2006
DOI: 10.1080/02724980543000123
|View full text |Cite
|
Sign up to set email alerts
|

Automatic–Heuristic and Executive–Analytic Processing during Reasoning: Chronometric and Dual-Task Considerations

Abstract: Human reasoning has been shown to overly rely on intuitive, heuristic processing instead of a more demanding analytic inference process. Four experiments tested the central claim of current dualprocess theories that analytic operations involve time-consuming executive processing whereas the heuristic system would operate automatically. Participants solved conjunction fallacy problems and indicative and deontic selection tasks. Experiment 1 established that making correct analytic inferences demanded more proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
148
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(159 citation statements)
references
References 81 publications
(167 reference statements)
7
148
1
3
Order By: Relevance
“…Furthermore, under the hypothesis that Type 2 processing is slower than Type 1 processing, participants who engage in more Type 2 processing should spend more time reasoning. Although some recent studies have used RT analyses to investigate the processes that underlie deductive reasoning (e.g., De Neys, 2006a;De Neys & Glumicic, 2008;Evans & Curtis-Holmes, 2005;Thompson, Prowse Turner, & Pennycook, 2011), none have used RT to assess individual differences in cognitive style. We predicted that those with faster RTs would have decreased accuracy on syllogisms and be more likely to hold specific religious beliefs.…”
Section: Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, under the hypothesis that Type 2 processing is slower than Type 1 processing, participants who engage in more Type 2 processing should spend more time reasoning. Although some recent studies have used RT analyses to investigate the processes that underlie deductive reasoning (e.g., De Neys, 2006a;De Neys & Glumicic, 2008;Evans & Curtis-Holmes, 2005;Thompson, Prowse Turner, & Pennycook, 2011), none have used RT to assess individual differences in cognitive style. We predicted that those with faster RTs would have decreased accuracy on syllogisms and be more likely to hold specific religious beliefs.…”
Section: Predictionsmentioning
confidence: 99%
“…In the present work, we therefore assessed response times (RTs) as a first step toward more directly probing differences in underlying processes during reasoning and associating these with both analytic performance and religious belief status. While RT is also presumably influenced by many factors, a selective increase in RT while reasoning has been taken as a sign of the use of Type 2 processes, because slower responding is generally expected under higher levels of deliberation (e.g., De Neys, 2006a;Evans, 2008). Thus, measuring RT allows us to shed light on a possible cognitive mechanism underlying the negative relation between analytic thinking and religious belief: response slowing.…”
mentioning
confidence: 99%
“…Thus far, only a few studies have examined response times in conditional reasoning (but see Barrouillet, Grosset, & Lecas, 2000;De Neys, 2006;Evans & Newstead, 1977). We tested our hypotheses in a truth-table task in which we presented adult participants with basic conditionals like ''If the star is yellow, then the circle is red'' and asked them to judge for each of the four logical cases if this case made the sentence true, false, or if it is impossible to tell if the sentence is true or false (indeterminate response).…”
Section: Tablementioning
confidence: 99%
“…Dual-task studies showed that participants tend to rely on simpler judgment and evaluation strategies or emotion-based choice processes under high concurrent cognitive load (e.g., De Neys, 2006;De Neys & Verschueren, 2006, Hinson, Jameson & Whitney, 2003Hinson & Whitney, 2006;Shiv & Fedorikhin, 1999), with working-memory resources being necessary to articulate a preference or judgment based on a more thoughtful consideration of the options and associated information (e.g., Evans, 2008;Stanovich & West, 2008). Moreover, individual-difference studies observed that participants with greater working memory capacity provide less subadditive probability judgments (Dougherty & Hunter, 2003) and that participants with better performance in executive functioning tests obtain better results in cognitively-demanding judgment and decision-making tasks (Del Missier, Mäntylä & Bruine de Bruin 2010Parker & Fischhoff, 2005).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%